Ditopic Receptors Based on Dihomooxacalix[4]arenes Bearing Phenylurea Moieties With Electron-Withdrawing Groups for Anions and Organic Ion Pairs - Miranda, Alexandre S.; Serbetci, Defne; Marcos, Paula M.; Ascenso, José R.; Berberan-Santos, Mário N.; Hickey, Neal; Geremia, Silvano (Frontiers in Chemistry, 2019)
Two bidentate dihomooxacalix[4]arene receptors bearing phenylurea moieties substituted with electron-withdrawing groups at the lower rim via a butyl spacer (CF3-Phurea 5b and NO2 Phurea 5c) were obtained in the cone conformation in solution, as shown by NMR. The X-ray crystal structure of 5b is reported. The binding affinity of these receptors towards several relevant anions was investigated by 1H NMR, UV-Vis absorption in different solvents, and fluorescence titrations. Compounds 5b and 5c were also tested as ditopic receptors for organic ion pairs, namely monoamine neurotransmitters and trace amine hydrochlorides by 1H NMR studies. The data showed that both receptors follow the same trend and, in comparison with the unsubstituted phenylurea 5a, they exhibit a significant enhancement on their host-guest properties, owing to the increased acidity of their urea NH protons. NO2-Phurea 5c is the best anion receptor, displaying the strongest complexation for F−, closely followed by the oxoanions BzO−, AcO− and HSO4−. Concerning ion pair recognition, both ditopic receptors presented an outstanding efficiency for the amine hydrochlorides, mainly 5c, with association constants higher than 109 M−2 in the case of phenylethylamine and tyramine.